2022
DOI: 10.1136/jitc-2022-005189
|View full text |Cite
|
Sign up to set email alerts
|

Automated, scaled, transposon-based production of CAR T cells

Abstract: BackgroundThere is an increasing demand for chimeric antigen receptor (CAR) T cell products from patients and care givers. Here, we established an automated manufacturing process for CAR T cells on the CliniMACS Prodigy platform that is scaled to provide therapeutic doses and achieves gene-transfer with virus-free Sleeping Beauty (SB) transposition.MethodsWe used an advanced CliniMACS Prodigy that is connected to an electroporator unit and performed a series of small-scale development and large-scale confirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Due to the decreased complexity of manufacturing processes and the better cargo capacity, transposon systems reduce the manufacturing costs and are more suitable for multi-targeted CAR-T cell manufacturing compared with viral vectors. Furthermore, transposon systems can be utilized on an automated process platform to generate clinical therapeutic doses of CAR-T cells, which will further promote the scale-up manufacturing of CAR-T cells and increase R/R patient access to CAR-T cell therapy ( 128 , 130 ). In addition, transposon-based CAR-T cells exhibit early memory T cell phenotype ( 128 ).…”
Section: Strategies To Improve Accessibility Of Car-t Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the decreased complexity of manufacturing processes and the better cargo capacity, transposon systems reduce the manufacturing costs and are more suitable for multi-targeted CAR-T cell manufacturing compared with viral vectors. Furthermore, transposon systems can be utilized on an automated process platform to generate clinical therapeutic doses of CAR-T cells, which will further promote the scale-up manufacturing of CAR-T cells and increase R/R patient access to CAR-T cell therapy ( 128 , 130 ). In addition, transposon-based CAR-T cells exhibit early memory T cell phenotype ( 128 ).…”
Section: Strategies To Improve Accessibility Of Car-t Cell Therapymentioning
confidence: 99%
“…Furthermore, transposon systems can be utilized on an automated process platform to generate clinical therapeutic doses of CAR-T cells, which will further promote the scale-up manufacturing of CAR-T cells and increase R/R patient access to CAR-T cell therapy ( 128 , 130 ). In addition, transposon-based CAR-T cells exhibit early memory T cell phenotype ( 128 ). Encouragingly, a recent study demonstrated that CRISPR-Cas9-mediated non-viral specifically targeted CAR-T cells were safe and effective in patients with R/R non-Hodgkin lymphoma (NHL) ( 56 ), indicating that CRISPR-Cas9 is a new tool for precise genome editing in CAR-T cell manufacturing and will facilitate the development of more gene-specific targeted CAR-T cells in the future ( 56 , 131 ).…”
Section: Strategies To Improve Accessibility Of Car-t Cell Therapymentioning
confidence: 99%
“…Different molecular (genotypic) assays, such as qPCR/dPCR, Nanostring, or next‐generation sequencing (NGS) DNA or RNA‐seq, could be used to monitor CAR‐T CK in cell therapy studies. Both Nanostring and RNA‐seq can be multiplexed for the quantitation of several gene targets in a single run 9,10 and RNA‐seq provides complete sequence information which could be useful in the discovery space. Overall, due to higher sensitivity, easy sampling, reproducibility, robustness, and cost/ease of handling a small number of targets, PCR‐based methods are widely used to monitor CAR‐T CK and preferred over NGS methodologies 11,12 .…”
Section: Methodsmentioning
confidence: 99%
“…However, these systems require well-trained staff and rigorous hygiene monitoring to avoid contaminations. Therefore, with the clinical successes of CAR-T cell therapies, the production has shifted not only in industrial facilities but also in academic institutions more and more to closed and semi- or fully-automated platforms ( 22 25 ). Most advances to the manufacturing platforms for CAR-T cells are likely transferable for the production of TCR-T cells with some modifications to the protocols.…”
Section: Manufacturing Of Genetically Engineered T Cellsmentioning
confidence: 99%
“…SB transposition has already been used successfully for the manufacturing of CD19 or SLAMF7 CAR-T cells in early clinical trials without severe toxicity ( 62 65 ). In addition, automation of SB transposition was feasible and could be very attractive for large-scale manufacturing ( 25 ). Although PB transposition was also successful for the manufacturing of CAR-T cells and even showed an inclination to promote the generation of desired TSCM CAR-T cells ( 66 , 67 ), a recent clinical trial observed the formation of CAR-T cell lymphoma in two out of ten patients ( 68 , 69 ).…”
Section: Manufacturing Of Genetically Engineered T Cellsmentioning
confidence: 99%